Kalimat dalam Teks Eksplanasi Siswa Kelas XI SMA N 3 Payakumbuh - Nadia Putri (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The purpose of this study was to describe the use of sentences in students' explanatory text in terms of four things. First, the use of sentences in terms of structural clarity, there are 192 (39.43%) errors. The use of sentences that are clearly active or passive structures (46 errors), the subject is not in the form of an explanation (11 errors), the predicate is not lost (33 errors), the information is not in the form of a subject (93 errors), and the subject is not lost (9 errors). Second, the use of sentences in terms of logical meaning, there are 98 (20.12%) errors. The use of inappropriate sentences is seen from the logical relationship between S and P (63 errors) and the logical relationship between the meaning of details (35 errors). Third, the use of sentences in terms of saving words is 105 (21.56%). Inaccurate use of the sentence on one subject from the same subject (14 errors), one word from several words is synonymous (no errors), and using the words needed to express the author's intent (91 errors). Fourth, the use of sentences in terms of the standard of words, there were 92 (18.89%) errors. This research is a qualitative research with an explanatory text sample of 25 students of class XI SMA Negeri 3 Payakumbuh. Based on these results it can be concluded that the use of sentences in the explanatory text of class XI students of SMA Negeri 3 Payakumbuh still has many errors.